Is it worth adopting DevOps practices in Global Software Engineering? Possible challenges and benefits - Grande, Rubén; Vizcaíno, Aurora; García, Félix O. (Computer standards and interfaces, 2024)
•Distributed and global software development has increased since COVID-19 pandemic.•DevOps is being adopted in distributed and global settings.•DevOps practices in global and distributed settings brings benefits and challenges.•Related DevOps practices, benefits and challenges in distributed and global settings. The software industry is adopting the DevOps paradigm to an increasingly frequent extent. In addition, the trend of developing software in a distributed manner greatly increased as a result of the COVID-19 pandemic, which forced team members from software companies to work remotely. We present the results of a Systematic Mapping Study (SMS) of how DevOps has been applied in distributed and global settings that adopts Global Software Development (GSD). The results were obtained from analysing 27 papers. The main conclusions obtained after carrying our SMS show that adopting DevOps in such settings by implementing certain practices brings several advantages to software companies, even though there are difficulties to be confronted when adopting DevOps in global and distributed contexts. Moreover, we (1) proposed definition of DevOps in distributed and global settings, (2) mapped the challenges detected with a list of well-known GSD risks and (3) mapped the benefits that can be obtained from applying certain practices identified and the challenges that should be overcame to obtain such benefits.